Gender Gaps and Corruption: The Phenomenon of NEET Women in Colombia - Henao Orozco, Nathalie (Universidad Pedagógica y Tecnológica de Colombia, 2024)
The theoretical-practical approach reveals the factors hindering women’s productivity in Colombia, the power dynamics between gender and corruption, and how these contribute to multidimensional poverty, which exacerbates the NEET problem. The study employed a descriptive qualitative methodology to analyze 85 documents that detail the characteristics, trends, and effects on the integral progress of women, which promote their unemployment status. The findings confirm that corruption and gender are the main causes of the NEET phenomenon. In conclusion, the data supports the expansion of the study to include analysis of categories such as multidimensional poverty, gender, and persistent corruption in our country.